Small area estimation for land use and land cover - Campos, Pedro (2019)
Small Area Estimation (SAE) is a part of statistical science that combines survey sampling and inference of finite populations with statistical modeling. The main objective of this paper is to analyze and test the implementation of different types of estimators of small domains in order to improve the quality of the estimates produced within the framework of the Farm Structure Survey (FSS) at NUTS III level. Under the EUROSTAT Land Use and Cover Area Statistical Survey (LUCAS) project, this is a fundamental tool for environmental studies, forestry and agricultural resource planning.